PEMIKIRAN OESMAN EFFENDI TENTANG MODERNISME DAN IDENTITAS SENI LUKIS INDONESIA - HIDAYATUL AZMI, Drs. Erfahmi, M.Sn., Drs. Wisdiarman, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this study were to (1) to find factors that influenced Oesman Effendi’s thinking about modernism and Indonesian painting identity, (2) explain how these factors influence Oesman Effendi’s thinking.The data of this study were interviews with people who have experience about Oesman Effendi and archives relating to Oesman Effendi. This study was conducted with a qualitative approach. Data was collected by using interview methods and literature studies. The findings of the study showed that cultural institution, Oesman Effendi as artist, and society influence his thinking about modernism and indonesian painting identity.Kata kunci : Oesman Effendi, modernisme, identitas seni lukis Indonesia